Primary Teachers' Principles for High-Quality Distance Teaching During COVID-19. Issue 5 (29th July 2022) - Mankki, Ville
ABSTRACT: School lockdowns in response to COVID-19 have forced teachers around the world to quickly and unexpectedly shift from face-to-face to distance teaching. The struggle with the forced transition has been even more severe in the lower levels of schooling than in higher education institutions, which had already established online course delivery before the crisis. The current paper investigates Finnish primary teachers' principles for high-quality distance teaching. Twenty primary teachers were interviewed in April 2020 during the fourth week of the two-month distance teaching period. The findings from phenomenographic analysis revealed that high-quality distance teaching at the primary level requires (1) relatedness, (2) design, (3) routine, and (4) control. This study illustrates the understanding of teachers' working in a basic education system ranked among the best in the world and thus provides valuable insights for developing instructional practices in distance education.